2011
DOI: 10.1309/ajcptus5exas6dkz
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of HPV-16 and HPV-18 Genotyping for the Triage of Women With High-Risk HPV+ Cytology-Negative Results

Abstract: The ATHENA (Addressing THE Need for Advanced HPV Diagnostics) HPV study evaluated the clinical usefulness of the cobas HPV Test (Roche Molecular Systems, Pleasanton, CA) for high-risk human papillomavirus (HR-HPV) testing (14 HR types) and individual HPV-16/HPV-18 genotyping in women undergoing routine cervical cytology screening in the United States. For the study, 47,208 women were recruited, including 32,260 women 30 years or older with negative cytology. All women with positive results for HR-HPV (n = 4,21… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
168
4
8

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 207 publications
(192 citation statements)
references
References 22 publications
12
168
4
8
Order By: Relevance
“…Triaging HPV-positive women with cytology and baseline HPV 16/18 genotyping has the advantage, compared with repeat cytology, that it identifies women with a high risk of underlying high-grade disease at baseline (5,15,18,19). Therefore, no additional doctor's visit is required, and no associated risk of losing women to follow-up during triage is present (20,21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Triaging HPV-positive women with cytology and baseline HPV 16/18 genotyping has the advantage, compared with repeat cytology, that it identifies women with a high risk of underlying high-grade disease at baseline (5,15,18,19). Therefore, no additional doctor's visit is required, and no associated risk of losing women to follow-up during triage is present (20,21).…”
Section: Discussionmentioning
confidence: 99%
“…This test used a cocktail of probes to detect 13 high-risk HPV genotypes: 16,18,31,33,35,39,45,51,52,56,58,59, and 68. Samples were considered positive if they had an HC2 outcome of 1 RLU/CO.…”
Section: Patients and Proceduresmentioning
confidence: 99%
“…Update of the ASCCP guideline recommended these cytological negative/HPV positive cases to be triaged by high-risk HPV typing (Apgar et al, 2009). The guideline was validated by a study of the ATHENA (Addressing THE Need for Advanced HPV Diagnostics) Study Group (Wright et al, 2011). In the present study, we compared the diagnostic characteristics of cytology analysis, HC2 HPV DNA test, TERC amplification test and their combinations to explore an optimal strategy for cervical cancer screening.…”
Section: Discussionmentioning
confidence: 99%
“…Among the 32 260 women aged 30 years or older with a negative Pap test result, the overall prevalence of HR-HPV detected with the cobas HPV Test was 6.7% and the overall prevalence rates for HPV16, HPV18, and 12 other HR-HPV genotypes were 1.0%, 0.5%, and 5.2%, respectively. 13 Women with ASC-US Pap test results had 32.6% HR-HPV-positive results (14 genotypes), with 8.2% HPV16 and 2.9% HPV18 prevalence. 10 Our 2014 survey data demonstrated that the median reporting rate of HPV16 and/or HPV18 positivity was 20.6% for women with negative Pap/positive HR-HPV test results regardless of age (Table 7) 16 The differences in these results may be reflective of the populations tested or the HPV platform.…”
Section: Ofmentioning
confidence: 95%